Effect of pre-sowing seed inoculation and foliar dressing on grain productivity and symbiotic activity of chickpea plants - M. Honchar (Рослинництво та ґрунтознавство)
The relevance of the study lies in the fact that in the context of the rapid pace of global climate change and war in Ukraine, farmers are interested in finding modern and innovative approaches that would allow obtaining high yields and optimising acreage in the Right-Bank Forest-Steppe zone, considering their reduction in those areas where sustainable chickpea grain cultivation was ensured. The purpose of the study was to substantiate and show the importance and necessity of using trace elements for foliar dressing, both in variations with and without seed inoculation. It was found that pre-sowing inoculation of chickpea seeds and the use of the trace element boron in double foliar top dressing during intensive growth (budding) and in the flowering phase at its initial stage provides a specific effect on the symbiotic activity of bacteria of the genus Rhizobium and grain productivity of chickpea plants. During pre-sowing seed treatment with bioinoculant BTU®-p and carrying out two foliar dressings in two different phases with microfertiliser Help Rost®-Boron, there was a significant increase in the weight and number of nodule bacteria, the weight of 1,000 seeds, germination energy, green mass, and plant height, which ultimately had an excellent effect on the final yield indicators of various variants compared to the control. The maximum weight and number of nodules during the research period was formed in the flowering phase, namely, at the end of this phase. The largest number of nodule bacteria was 38.2 units/plant with a weight of 625.1 mg/plant on roots and root hairs was recorded in the variant with sowing of the Triumph variety, where two foliar dressings with microfertilisers and pre-sowing seed treatment with BTU®-p inoculant were used, which as a result exceeded the control by 11.2 units/plant and 24.9 mg/plant in the same growing season of the plant. It was found that the use of pre-sowing inoculation of chickpea seeds and foliar dressing during two different phases of vegetation allowed increasing the yield to 3.07-3.18 t/ha